OCCURRENCE OF SOLENOSTOMA CYNOPTERUM SLEEKER 1854 FROM MBUDYA ISLAND, DAR-ES-SALAAM - Pratap, H B (Indian Journal of Fisheries, 2011)
During a recent visit to Mbudya Island, south of Dar-es-salaam, theauthor came across a Solenostoma cynopterum Sleeker at the periphery of atidal pool. This was initially mistaken for the seagrass, Thalassodendron. Thesingle specimen thus got was brought to the laboratory and fixed in 10% formalin.